Effects of defoliation from an outbreak of the teak skeletoniser, Paliga damastesalis walker (Lepidoptera: Crambidae), on the growth of teak, Tectona grandis L. - Lim, Wui Oi; Ibrahim, Yusof; Kirton, Laurence G.; Abood Harris, Faizah (Universiti Putra Malaysia Press, 2010)
The effects of defoliation by the teak skeletoniser Paliga damastesalis Walker (Lepidoptera: Crambidae) on a six-month old stand of teak Tectona grandis L. was evaluated on the subsequent year-long growth in the field. Defoliation did not exceed 10%. It had a transient negative effect on post-defoliation height increment and new leaf production of up to two and three months of growth. However, defoliation severity significantly affected collar diameter increment up to the seventh month. A peak in the mean monthly growth increments for new leaf production occurred in April, followed by collar diameter increment in June and height in July. In addition, a peak in one of these three growth parameters also corresponded with a trough in the other or both of the other parameters; as such, the height increment peaked with a concomitant trough in collar diameter increment a month later. As for the remaining period of the dry season after July, new leaf production remained at a constant low level, while increments for both the height and collar diameter were found to decrease. Tree recovery appeared rapid with regard to these growth parameters, thus the impact of defoliation was generally and relatively negligible on the growth parameters measured.